Character Education for the Young Generation Through the Mamaca Madura School In Situbondo Regency - Agustina Dewi Setyari; Akhmad Sofyan; Panakajaya Hidayatullah; Dewi Angelina (LPPM UIKA Bogor, 2022)
Mamaca is a tradition of the Madurese community in the form of reading texts in the form of poetry by singing them so that mamaca must use beautiful or archaic language. The stories in the Mamaca text come from babad stories, stories of prophets, stories of historical figures, as well as stories taken from fictional stories or figures that are filled with petotor or advice. Based on the various contents of the text, making mamaca is very important for strengthening the character of young people, one of them in Situbondo. Mamaca is one of the intangible inheritances (WTB) in Situbondo. The problem that then arises is the difficulty of regenerating the mamaca tradition. Through the piloting of the Mamaca School in the Arjasa Situbondo District, it is hoped that the Mamaca tradition will continue to grow rapidly among the younger generation. With the acceptance of the mamaca tradition in the younger generation, it is hoped that character education can be carried out through this tradition.